Collaborative initiatives of digital local content among public libraries: a structured literature review / Nik Norfauzieana Mohd Zaki, Norshila Shaifuddin and Wan Nor Haliza Wan Mokhtar - Mohd Zaki, Nik Norfauzieana; Shaifuddin, Norshila; Wan Mokhtar, Wan Nor Haliza (Faculty of Information Management, 2022)
In cutting-edge technology, providing access to digital collections to the local communities is inevitable for public libraries. Public libraries' initiatives toward creating local digital content have become possible through the collaborative efforts between Malaysian public libraries. This paper attempts to critically examine the previous literature, with the objective of identifying the main themes of research on the collaborative initiatives of local digital content among public libraries. Data were collected based on the analysis in all major journals in the library collaborative initiatives area. A total of 53 was undertaken using searches of Scopus and Web of Science (WOS) database, were included in this review, covering three major research themes, that is, the collaboration and local digital content issues, collaborative initiatives in digital local content and theories and framework related to collaboration and local digital content. The dimensions of collaborative initiatives identified from the review indicate that future research should focus on the six dimensions of collaborative initiatives: participants, the focus of interaction, the context of collaboration, features of collaboration, collaborative processes, and perceived outcomes of collaborations. Additionally, results differ in various contexts, and there is no universally accepted framework specifically for the digital local content creation collaborative initiatives. However, the theories and framework related to collaboration and local digital content from previous research provide public libraries with a guide to the factors that may affect the collaborative initiatives and help them develop effective collaborative strategies. Suggestions for future research are provided based on thematic considerations.